Renin-Angiotensin System overactivation in polycystic ovary syndrome, a risk for SARS-CoV-2 infection? - Abu Saleh Md Moin (6189512) (2020)
Background The SARS-CoV-2 coronavirus gains entry to target cells via the angiotensin-converting enzyme 2 (ACE2) receptor present on cells in blood vessels, lungs, heart, intestines, and kidneys. Renin-Angiotensin System (RAS) overactivity has also been described in metabolic syndrome, type 2 diabetes (T2D) and obesity, conditions shared by women with polycystic ovary syndrome (PCOS) We hypothesized that RAS overactivity may be present in PCOS. Methods We determined plasma levels of RAS-related proteins in a cohort of age matched control women (n = 97) and women with PCOS (n = 146). Plasma levels of RAS-related proteins (ACE2, Renin and Angiotensinogen (AGT)) were determined by Slow Off-rate Modified Aptamer (SOMA)-scan plasma protein measurement. Results PCOS women had a higher BMI (p < 0.001), systolic (p < 0.0001) and diastolic (p < 0.05) blood pressure, waist circumference (p < 0.0001), testosterone (p < 0.0001), free androgen index (p < 0.0001) and CRP (p < 0.0001). Renin was elevated in PCOS (p < 0.05) and angiotensinogen was lower in PCOS (p < 0.05), indicating overactivity of the RAS system in PCOS. ACE2 levels were lower in PCOS (p < 0.05), suggesting that PCOS women are at risk for development of hypertension. Conclusion RAS proteins levels differed between PCOS and control women, suggesting that the insulin resistance inherent in PCOS may predispose these women to more severe COVID-19 infection. Other Information Published in: Metabolism Open License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.metop.2020.100052